P114 Non-tuberculous mycobacteria–An increasing problem with many companions. (14th November 2013) - Karampini, E; Groves, C; Milburn, HJ; Barker, RD; Breen, RAM; Perrin, FMR
Abstract : Introduction: Infections secondary to non-tuberculous mycobacteria (NTM) are emerging with increasing frequency in various clinical settings. The determination of the clinical and prognostic significance of NTM isolates remains challenging and, in the absence of large trials, the evidence around the different therapeutic options is limited[1]. We aimed to identify the number of patients with single/multiple NTM isolates in our hospitals and evaluate their complexity with respect to coexistent microbiology. Method: A retrospective case review of patients in whom NTM were isolated over the last two years in two large teaching hospitals. Results: 195 patients were diagnosed with an NTM within the specified time period. Of those, 29 patients (14.8%) had cystic fibrosis (CF) and 11 patients (5.6%) were HIV-positive. In the non-CF population, in 112 of 166 patients (67.5%) NTM were isolated in 1 sample, in 24 patients (14.5%) in 2 samples and in 30 patients (18%) in 3 or more samples. In 8 patients (4.8%) 2 or more different NTM species were isolated in the same samples. The NTM source was: sputum in 130 patients (78.3%), bronchial washings in 23 patients (13.8%) and other pulmonary/non-pulmonary sites in 13 patients (7.9%). Table 1 shows the NTM species isolated. 61 patients (36.7%) were co-infected with other organisms; most commonly with Pseudomonas aeruginosa, Staphylococcus aureus and Haemophilus influenzae. Co-infection with other organisms was not related to the NTM species, or to the number of NTM isolates. 114 patients (68.7%) were reviewed by a respiratory physician; this included all patients with 3 or more NTM isolates. 122 patients (73.5%) underwent CT imaging. 36 patients (21.7%) were commenced on treatment. Conclusion: NTM infection is an increasing and often complex challenge in respiratory medicine that requires specialist input. Further studies are needed to clarify whether co-infection with other organisms is related to the nature (e.g. bronchiectasis, cavitation) or severity of respiratory disease. References: Griffith DE et al ; "An Official ATS/IDSA Statement: Diagnosis, Treatment, and Prevention of Nontuberculous Mycobacterial Diseases", AJRCCM 175: 367–416 (2007)